Housing Unaffordability and Adolescent Subjective Well-Being in China - Peng Nie; Qiaoge Li; Alfonso Sousa-Poza (Institute of Labor Economics (IZA), 2022)
Using the 2010-2018 waves of the China Family Panel Studies, we investigate the impact of housing unaffordability on subjective well-being (SWB) among Chinese adolescents aged 10-15. Using a combined methodology of propensity score matching and fixed effects and instrumental variable estimations, we show that housing unaffordability leads to higher levels of depression, with more pronounced impacts among older adolescents (aged 13-15), those from migrant and urban families, and those living in regions with high housing prices and expensive living costs. These results are robust not only to alternative housing unaffordability and SWB measures but to a series of estimation approaches that control for endogeneity. An additional structural equation modelling analysis of underlying pathways further reveals that this housing unaffordability-SWB relation is mediated by paternal depression and (lower) adolescent trust in parents.
Keywords: D10; I10; I31; J13; R21; 330; housing unaffordability; depression; adolescents; China